2007
DOI: 10.1021/np070091e
|View full text |Cite
|
Sign up to set email alerts
|

Phenalenone-Type Compounds from Musa acuminata var. “Yangambi km 5” (AAA) and Their Activity against Mycosphaerella fijiensis

Abstract: Two perinaphthenone-type compounds (1 and 2) were isolated together with four known phenylphenalenones (3-6) from the rhizomes of Musa acuminata var. "Yangambi km 5". The structures of the new phenalenones were assigned as 2-hydroxy-1H-phenalen-1-one (1) and 2-methoxy-1H-phenalen-1-one (2) on the basis of their spectroscopic data and were confirmed by synthesis. Compounds 1 and 2 displayed significantly enhanced activity against Mycosphaerella fijiensis in comparison with other phenylphenalenones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 15 publications
2
74
0
1
Order By: Relevance
“…The activity of phenylalanine ammonia lyase (EC 4.3.15), the entry-point enzyme of the phenylpropanoid pathway, is correlated to the biosynthesis of specific phenylpropanoids involved in defense and was substantially induced in nematode infected roots of Ykm5 (19). Phenylphenalenone-related compounds show biological activity against bacteria, fungi, algae, and diatoms (18,(20)(21)(22). The formation of these compounds has been elicited in banana leaves by Mycosphaerella fijiensis (Black Sigatoka leaf streak disease), in the fruit peels by Colletotrichum musae (anthracnose disease), and in roots and rhizomes by F. oxysporum f. sp.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The activity of phenylalanine ammonia lyase (EC 4.3.15), the entry-point enzyme of the phenylpropanoid pathway, is correlated to the biosynthesis of specific phenylpropanoids involved in defense and was substantially induced in nematode infected roots of Ykm5 (19). Phenylphenalenone-related compounds show biological activity against bacteria, fungi, algae, and diatoms (18,(20)(21)(22). The formation of these compounds has been elicited in banana leaves by Mycosphaerella fijiensis (Black Sigatoka leaf streak disease), in the fruit peels by Colletotrichum musae (anthracnose disease), and in roots and rhizomes by F. oxysporum f. sp.…”
Section: Significancementioning
confidence: 99%
“…The formation of these compounds has been elicited in banana leaves by Mycosphaerella fijiensis (Black Sigatoka leaf streak disease), in the fruit peels by Colletotrichum musae (anthracnose disease), and in roots and rhizomes by F. oxysporum f. sp. cubense (Panama disease) and R. similis (16,18,21,23).…”
Section: Significancementioning
confidence: 99%
“…About antifungal mechanisms, it was reported that the compound 22 is a fungal endo-β-(1,3)-glucanase inhibitor (Vargas-Arispuru et al, 2009). Others active compounds (Figure 1) are acetylenic lactone (27) (Queiroz et al, 2012), 2-phenylethanol ester (28) (Labbé et , 2005), and the unusual 2-hydroxy-1-H-phenalen-one (29) and 2-methoxy-1-H-phenalen-one, which are fungicides against Colletotrichum, Cladosporium, and Mycosphaerella, respectively (Otálvaro et al, 2007). Other compound also toxic to Colletotrichum was the known glucosinolate glucoraphanin, isolated from Brassica oleracea (Lara-Viveros et al, 2014) Plants are able to produce proteinaceous compounds, between those described with fungicide activity are lectins (glycoproteins that agglutinate and immobilize microorganisms) and microbial proteinase inhibitors (inhibit enzymes that degrade plant cell walls).…”
Section: Gaeumannomyces Graminismentioning
confidence: 99%
“…Phenylphenalenones are a group of polycyclic plant natural products mainly occurring in the Haemodoraceae [1][2][3][4] and the Musaceae [5][6][7][8]. There is ample evidence that the biosynthesis of phenylphenalenones, first discussed by Thomas in 1961 [9], involves a diarylheptanoid, which undergoes cyclization to form the substituted tricyclic phenylphenalenone.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion could proceed either by chemical reaction in vitro [10], starting from compound 1a, or in vivo after administration to plant material [11]. [2][3][4][5][6][7][8][9][10][11][12][13] C]1-(3,4-Dihydroxyphenyl)-7-phenylhepta-4,6-dien-3-one (1a), when administered to cultured roots of Anigozanthos preissii, was smoothly converted to [8][9][10][11][12][13] C]anigorufone [11]. …”
Section: Introductionmentioning
confidence: 99%